Pengaruh Profitabilitas, Ukuran Perusahaan, Pertumbuhan Perusahaan Dan Leverage Terhadap Penerimaan Opini Audit Going Concern (Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi di BEI Periode 2017-2019) - Ni Kadek Suartika Yanti; Luh Kade Datrini; Gde Deny Larasdiputra (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This research is a quantitative study that aims to empirically the effect of profitabiliy, company size, company’s growth and leverage on the attainment of going concern audit opinion (at Manufacturing Good Consumer Industry Sector Listed on the BEI Period 2017-2019). This study used secondary data with analysis method is logistic regression analysis. The result of this research is the profitability and company size does not have an effect on going concern audit opinion. The companys’s growth have an negative effect on going concern audit opinion. The leverage have an positif effect on going concern audit opinion.